Inhibition of neogenin fosters resolution of inflammation and tissue regeneration - Schlegel, Martin (J Clin Invest, 2018)
The resolution of inflammation is an active process that is coordinated by endogenous mediators. Previous studies have demonstrated the immunomodulatory properties of the axonal guidance proteins in the initial phase of acute inflammation. We hypothesized that the neuronal guidance protein neogenin (Neo1) modulates mechanisms of inflammation resolution. In murine peritonitis, Neo1 deficiency (Neo1(–/–)) resulted in higher efficacies in reducing neutrophil migration into injury sites, increasing neutrophil apoptosis, actuating PMN phagocytosis, and increasing the endogenous biosynthesis of specialized proresolving mediators, such as lipoxin A4, maresin-1, and protectin DX. Neo1 expression was limited to Neo1-expressing Ly6C(hi) monocytes, and Neo1 deficiency induced monocyte polarization toward an antiinflammatory and proresolving phenotype. Signaling network analysis revealed that Neo1(–/–) monocytes mediate their immunomodulatory effects specifically by activating the PI3K/AKT pathway and suppressing the TGF-β pathway. In a cohort of 59 critically ill, intensive care unit (ICU) pediatric patients, we found a strong correlation between Neo1 blood plasma levels and abdominal compartment syndrome, Pediatric Risk of Mortality III (PRISM-III) score, and ICU length of stay and mortality. Together, these findings identify a crucial role for Neo1 in regulating tissue regeneration and resolution of inflammation, and determined Neo1 to be a predictor of morbidity and mortality in critically ill children affected by clinical inflammation.